Enhancing graduate AI education through practical and values-driven curriculum integration - Zhong, Meiqi; Wei, Linjing; Mo, Henghui (Frontiers in Education, 2025)
IntroductionWith the rapid advancement of artificial intelligence (AI) technologies, there is a growing demand in graduate education for highly skilled, application-oriented professionals equipped with both technical expertise and strong ethical values. However, traditional AI curricula often lack effective integration of practical training and values-based education.MethodsThis study describes the design and implementation of an integrated curriculum for AI master's students, combining systematic industry needs assessment, curricular reform, and pedagogical innovation. The program emphasizes the cultivation of practical skills alongside values-oriented education—specifically professional responsibility, ethical awareness, and societal engagement—through course planning, case-based learning, project-driven instruction, and interdisciplinary collaboration. Multiple evaluation tools were employed, including student and faculty surveys, focus group interviews, and analysis of performance metrics such as project outcomes and academic competition results.ResultsEvaluation results demonstrate that the integrated curriculum significantly enhances students' initiative, critical thinking ability, and sense of social responsibility. Students not only achieved higher technical competence but also exhibited improved holistic qualities, as reflected in project achievements and external competition performance.DiscussionThe core innovation of this model lies in the seamless integration of ethical and societal considerations into technical training. Although the case study is limited to a single institution, the model provides valuable insights for AI education reform and high-quality talent cultivation. These findings establish a theoretical foundation for the adaptation and application of such integrative approaches across diverse educational settings.